How the Colorado Forest Restoration Institute can help - Binkley, Dan, author (Colorado State University. Libraries, 2007)
Presented at the Can forests meet our energy needs? The future of forest biomass in Colorado conference, February 21, 2008, Colorado State University, Fort Collins, Colorado. Dr. Dan Binkley has worked on ecosystem productivity and nutrient cycling for 25 years, blending applied and basic perspectives in his research and teaching. Some of the applied perspectives have focused on sustaining the productivity of forests by sustaining soil fertility and providing useful information in textbooks and courses for people who manage forests. His basic research perspectives include long-term changes in vegetation and soils (along rivers, with tree invasion of tundra as climate warms, and in common-garden experiments), and fundamental controls on ecosystem productivity over time (using plantations of Eucalyptus species in Hawaii and Brazil as model systems). Dr. Binkley has been at Colorado State University for 20 years, teaching courses on a wide range of topics in ecology and sustainable forestry. He was the Director of CSU's cross-campus Graduate Degree Program in Ecology for 12 years, and is now the Director of the new Colorado Forest Restoration Institute. Prior to CSU, Dr. Binkley spent 5 years as an assistant professor at Duke University's School of Forestry and Environmental Studies. He holds degrees from Oregon State University (1982 PhD in forest ecology, with minors in soil science and botany), the University of British Columbia (1980 M.S. in forest ecology), and Northern Arizona University (1976 BSF in Forest Management).